Prevalence of Fabry Disease among Patients with Parkinson's Disease. (24th January 2022) - Lackova, Alexandra; Beetz, Christian; Oppermann, Sebastian; Bauer, Peter; Pavelekova, Petra; Lorincova, Tatiana; Ostrozovicova, Miriam; Kulcsarova, Kristina; Cobejova, Jana; Cobej, Martin; Levicka, Petra; Liesenerova, Simona; et al.
Abstract : Background . An increased prevalence of Parkinson's disease (PD) disease has been previously reported in subjects with Fabry disease (FD) carrying alpha-galactosidase (GLA) mutations and their first-line relatives. Moreover, decreased alpha-galactosidase A (AGLA) enzymatic activity has been reported among cases with PD compared to controls. Objective . The aim of our study was to determine the prevalence of FD among patients with PD. Methods . We recruited 236 consecutive patients with PD from February 2018 to December 2020. Clinical and sociodemographic data, including the MDS-UPDRS-III scores and HY stage (the Hoehn and Yahr scale), were collected, and in-depth phenotyping was performed in subjects with identified GLA variants. A multistep approach, including standard determination of AGLA activity and LysoGb3 in males, and next-generation based GLA sequencing in all females and males with abnormal AGLA levels was performed in a routine diagnostic setting. Results . The mean age of our patients was 68.9 ± 8.9 years, 130 were men (55.1%), and the mean disease duration was 7.77 ± 5.35 years. Among 130 men, AGLA levels were low in 20 patients (15%), and subsequent Lyso-Gb3 testing showed values within the reference range for all tested subjects. In 126 subsequently genetically tested patients, four heterozygous p.(Asp313Tyr) GLA variants (3.2%, MAF 0.016) were identified; all were females. None of the 4 GLA variant carriers identified had any clinical manifestation suggestive of FD. Conclusions . The results of this study suggest a possible relationship between FD and PD in a small proportion of cases. Nevertheless, the GLA variant found in our cohort is classified as a variant of unknown significance. Therefore, its pathogenic causative role in the context of PD needs further elucidation, and these findings should be interpreted with caution.